Habitat suitability, coverage by protected areas and population connectivity for the Siamese crocodile Crocodylus siamensis Schneider, 1801. Issue 4 (13th June 2014) - Ihlow, Flora; Bonke, René; Hartmann, Timo; Geissler, Peter; Behler, Natascha; Rödder, Dennis
Abstract With estimates of fewer than 1000 mature individuals in the wild, the critically endangered Siamese crocodile, Crocodylus siamensis Schneider, 1801, is one of the least known and at the same time most threatened crocodilian species in the world. Populations have already been depleted to approximately 20% of their former size with habitat destruction, alterations, and loss being the main drivers of population declines. Habitat suitability models were computed using a combination of bioclimatic and remote sensing variables as environmental predictors to evaluate habitat suitability and coverage by designated protected areas across the species' distributional range. In addition, population connectivity as well as current and future habitat fragmentation through dam construction was assessed by performing population connectivity models. Habitat suitability models show the spatial extent of suitable habitat to be high (46%), although only a small proportion is covered by designated reserves (11%). Population connectivity models showed remnant populations to be highly fragmented. Considering habitat suitability, coverage of reserves and population connectivity the lower Mekong River Basin stretching from the Xe Champhon and Xe Xangxoy rivers in Lao PDR to the Srepok and Sekong rivers in eastern Cambodia seem to be particularly important for future conservation prioritization for C. siamensis. The presently established protected area network is unsatisfactory in terms of size and population connectivity and needs to be significantly improved to successfully sustain viable populations of the critically endangered Siamese crocodile in the future. Copyright © 2014 John Wiley & Sons, Ltd.